Comparative Review on Occurred Defect Data and Term of Warranty Liability to Landscape Work in Apartment Building Complex - Park, Junmo; Seo, Deokseok (International Journal of Engineering and Technology, 2018)
Background/Objectives: In defect lawsuits for apartment, the term of warranty liability is the important legal standards that distinguish responsibility for said defects. However, the term of warranty liability has been criticized as it has no setting basis for itself and it is unrealistic.Methods/Statistical analysis: Therefore, this study examined the problems of the current legislation and sought a rational basis system to supplement them. The scope of the study was to compare and analyze the tendency of occurrence of defects and term of warranty liability, mainly in the landscape work of apartment building complexes. The results are summarized as follows.Findings: The total number of landscaping defects was the highest in the first year, but relatively low compared to other facility work. In addition, other facility works mainly resulted in defects up to the first two years, whereas that of landscape work occurred over four years later. Although the detail work of the landscape works is somewhat different, in general, the cumulative rate of occurred defects reaches 95% in the third to fourth years while it confirmed the eighth year for additional landscape appurtenant work.Improvements/Applications: Therefore, the term of warranty liability should be properly established considering the tendency of defects in landscape work.Â Â